"Subaltern issues‟ in Mamoni Raisam Goswami‟s The Moth Eaten Howdah of the Tuskar - Payeng, Devid (International Journal of Psychosocial Rehabilitation, 2020)
Indira Goswami is one of the most important figures in contemporary Indian literature. She has devoted her writings for the cause of the marginalized women. She was honored with the “Sahitya Akademi Award” in 1983 for the novel The Rusted Sword, the “Assam Sahitya Sabha Award” in 1988, and in the year 2000 she was awarded with the country’s highest literary prize the Jnanpith Award. Her novel originally published as Dontal Hatir Une Khowa Howdah in 1986 was translated by the author herself in 2004 as the The Moth Eaten Howdah of the Tusker.